THE CHALLENGE OF TREATING EPILEPSY IN PREGNANCY: MATERNAL AND OFFSPRING PERSPECTIVES - E. Babikir M.D, Haydar (مجلة الجزيرة للعلوم الصحية; مجلد 6 عدد 1 (2010), 2010)
Epilepsy is a common medical and social disorder and usually defined as a tendency to recurrent seizures. Freedom from seizures is the ultimate goal in treatment of patients with epilepsy. At the same time, the side effects of antiepileptic drugs (AEDs) should not outweigh the benefits of treatment. This is particularly important in epileptic women who wish to become pregnant. Those women have a higher risk for pregnancy-related complications. For babies whose mothers take AEDs, the risk of birth defects is 4 to 8 percent, compared with 2 to 3 percent for controls. The risk seems to be highest when multiple AEDs are taken, but without medication, uncontrolled seizures may deprive the baby of oxygen. Seizures can also increase the risk of miscarriage or stillbirth. By working with her physicians, a woman with epilepsy can become pregnant and have a happy outcome. In the Sudan we lack national epidemiological studies using standardized definitions and case ascertainment methods on epilepsy as general and in pregnancy, but according to the WHO the number of people with epilepsy is high in most regions of the world. The mean number per 1000 population is 8.93 (SD 8.14, median 7.59). This knowledge is essential for the identification of needs and the planning of appropriate services. This a thorough review of more than 40 articles published over the last 10 years. However, it is not a complete reference for designing a protocol for the management of epilepsy in pregnant women. It aims at discussing current management of epilepsy and pregnancy, including the fetal outcome and teratogenicity of AEDs. It is part of a series mandated by the Gezira Epilepsy Care Program (GECP), to obtain baseline data for a community-adapted epilepsy education and awareness program.